Rubber Tyred Gantry (RTG) Failure Analysis Using FMEA Method at PT. Kaltim Kariangau Terminal Balikpapan - Fitriah, Rifkah; Andi Ningrat; Dwi Wahyuni Rahman; Andi Rachmianty AM; Muslihati; Wardina Suwedy (Indonesian Journal of Maritime Technology, 2024)
Failure Mode and Effect Analysis (FMEA) is a method designed to evaluate system designs by identifying various failure modes of a system, which consists of multiple components, and analyzing their impacts on the system's reliability. The primary goal of FMEA is to identify and address key issues at every stage of the design and production process to prevent defective products from reaching customers, thereby safeguarding the company’s reputation. This study aims to identify the types of damage occurring in Kalmar-brand Rubber Tyred Gantry (RTG) equipment at PT. Kaltim Kariangau Terminal Balikpapan and analyze these failures using the FMEA method. Data collection was conducted through field observations, interviews, and documentation. The FMEA calculations also include repair recommendations for each identified failure. Based on the analysis, several failures were found to rank highest in severity for each piece of equipment. For RTG 07, the most critical failure was the "Trouble Hoist," requiring corrective actions such as repairs to the motor system, brakes, and gearbox.